Near field MIMO array imaging algorithm based on spherical wave decomposition - Rongqiang Zhu; Jianxiong Zhou; Qiang Fu (2016 CIE International Conference on Radar (RADAR), 2016)
Multiple-input-multiple-output (MIMO) array imaging is more challenging than the monostatic configuration because the incident and reflected path are different. In FFT-based MIMO array imaging algorithms, rearrangement in wavenumber domain to reduce dimension is implemented which has low efficiency and restricts the sampling steps in spatial frequencies. This paper proposes a novel wavenumber domain imaging algorithm based on spherical wave decomposition. This algorithm uses FFT to transform the measurements into wavenumber domain for compensation, and then the spectrum is retransformed to reconstruct image by FFT and coherent accumulation. It avoids the rearrangement operation and preserves the high efficiency of the FFT-based method, and can be implemented for transmitting and receiving arrays of different length. The imaging performance is demonstrated by simulation.